Comparison of Two Approaches of Resolving Power Sharing Error in Droop Based DC Microgrids - Hooman Khamooshpoor; Mehdi Baharizadeh; Mohammad Hossein Ershadi (Majlesi Journal of Electrical Engineering)
DC microgrids have gained extensive attention in the recent years. In the islanded mode of operation power sharing between sources is required. The power sharing usually is provided by employing P-V droop characteristics while the voltage local property results in power sharing error. In this paper two decentralized approaches for resolving power sharing error are studied and compared. In the first approach, sources employ proper virtual resistance. In second approach, droop characteristics are realized in the Point of Common Coupling (PCC). It is shown that by using second approach, the voltage drop is reduced and equally the voltage quality is improved. It is discussed that the reason is bypassing the voltage drop associated with the sources output resistance in the second approach. Time domain simulations of a test DC microgrid are provided to verify the results.